Candidate Race, Partisanship, and Political Participation: When Do Black Candidates Increase Black Turnout?. (June 2015) - Fairdosi, Amir Shawn; Rogowski, Jon C.
A sizable literature in American politics documents increased levels of voter turnout among black citizens when coracial candidates are on the ballot or hold office. However, due to a paucity of black Republican candidates, existing research has been unable to identify whether increased participation occurs irrespective of the candidate's partisanship. Using data from the 2010 Cooperative Congressional Election Study, we find that, while the presence of a black Democratic House candidate was associated with increased black voter turnout, there was no association between black Republican candidates and black turnout. These results are robust to model specification, issues of statistical power, and contextual differences across districts. We report further evidence that black citizens' perceptions of black candidates' ideologies and character traits differed substantially based on the candidate's party. Our results have implications for understanding how citizens engage in politics when salient political identities come into conflict. The results further suggest that Republican efforts to recruit black candidates are unlikely to mobilize black voters.